Peran Strategis Mahasiswa dalam Mengembangkan Bahasa Arab di Dunia Usaha dan Industri - Sovia Fahraini; Muhammad Fikri Almaliki (Al-Wazan: Journal of Arabic Education, 2023)
Along with the times, students are required to be able to think creatively and make innovative contributions to face industry 5.0. This is because, in reality, there are many graduate students who are not ready to face the world of work, lack creativity, so they rely on working in private institutions or government-owned institutions. Meanwhile, if this continues, there will be many graduates who end up being unemployed. So, the Kediri State Islamic Institute provides an Entrepreneurship Lecture Program (KWU) to help students, especially in Arabic language education study programs, channel their interests and talents as well as add expertise in business and industry. Arabic language education students are not only prepared to become teachers, but can also contribute to entering the world of business and industry and contribute to providing jobs for others. Thus, researchers contribute to examining how the strategic role of students in developing Arabic in the world of business and industry. This study uses descriptive qualitative methods using questionnaires, interviews and observations to obtain valid data results. The existence of the Entrepreneurship Lecture Program (KWU) is a form of forum for students to channel and develop their knowledge so that it can become a provision to play their role in the world of business and industry. KWU is also a solution to prepare students, especially at IAIN Kediri, to become graduates who are ready to enter the business and industrial sectors. In the Arabic Language Education Study Program, the existence of entrepreneurship can help develop Arabic to international level.